OC-038 The age-dependent relationship of dietary antioxidant intake and the risk of barrett's oesophagus and oesophageal adenocarcinoma: a uk prospective cohort study using micronutrient data from food diaries and serum biomarkers. (22nd June 2015) - Kang, Jh-E; Yates, M; Luben, R; Cheong, E; Alexandre, L; Igali, L; Khaw, K-T; Hart, A
Abstract : Introduction: The development of both Barrett's oesophagus (BO) and oesophageal adenocarcinoma (OAC) may involve oxidative stress. We investigated whether the antioxidants vitamins C and E, selenium, zinc and carotene were associated with a decreased risk of BO and OAC, in the same population, using nutritional information from 7-day food diaries, the most accurate questionnaire-based methodology. Method: A cohort of 23, 658 initially well individuals, aged 40–74 years, enrolled in the European Prospective Investigation of Cancer-Norfolk Study completed 7-day food diaries. Serum vitamin C levels were measured. They were monitored till December 2008 to identify those diagnosed with BO and OAC, confirmed through reviewing medical records. Hazard ratios (HRs) for these two conditions were estimated for each quintile of intake, corrected for age, gender, BMI and smoking. The analyses were repeated in participants younger and older than 65 years at recruitment, the mid-point of the peak prevalence of BO. Results: 92 participants who developed BO and 61 OAC were compared with 3712 randomly selected controls. In the whole cohort, and in those aged above 65 years at recruitment, there were no associations between any antioxidant and the risk of developing BO or OAC. However, in participants aged less than 65 years at recruitment, for BO statistically non-significant inverse associations were observed between all quintiles of food-diary assessed vitamin C intake (highest vs lowest quintile HR = 0.49, 95% CI = 0.20–1.22), with a significant inverse trend across quintiles for serum vitamin C and BO risk (Trend HR = 0.76; CI = 0.59–0.97; P = 0.03). For the development of OAC in participants recruited when less than 65 years, there were significant inverse trends across quintiles for both dietary vitamin C intake (Trend HR = 0.65; CI = 0.44–0.96; P = 0.03) and serum vitamin C (Trend HR = 0.54; CI = 0.33–0.89; P = 0.02). In this group there was a borderline significant inverse trend between vitamin E intake and OAC (Trend HR = 0.70; CI = 0.48–1.01; P = 0.06), but no associations with zinc, selenium or carotenes. Conclusion: Vitamin C deficiency may be involved in the aetiology of BO and possibly OAC, and may influence carcinogenesis below 65 years of age. Vitamin E may prevent the malignant progression of BO to OAC, again in younger individuals. Vitamins C and E levels should be measured in future aetiological studies for these conditions and randomised controlled trials of their use to prevent the malignant progression of BO may be justified. Disclosure of interest: None Declared.